The Combined Effect of Integrated Naturopathy and Yoga Management with Cold Hip Bath for Ten Days on Glycemic Profile and Body Composition in Middle-aged Diabetic Patients - Vedaharshni P; Sujatha K J; Prashanth Shetty; Geetha B Shetty (Indian Journal of Integrative Medicine, 2021)
Background and Purpose: Chronic hyperglycaemia and central obesity play a major role in the pathophysiology of Type 2 Diabetes Mellitus (T2DM). We examined the effects of cold hip bath (CHB) with Integrated Naturopathy and Yoga treatment protocol (INY) on glycaemic profile and body composition in middle-age T2DM individuals. Materials and Methods: Participants were randomly assigned into study group (n = 50) and control group (n = 50), participants in both the group received INY treatment protocol for 10 days. Subjects in the study group received INY treatment protocol ? CHB for 20 minutes for 10 days. Glycaemic profile and body composition parameters were evaluated before and following the interventions. Results: Fasting Blood Glucose (FBG), Post Prandial Blood Glucose (PPBG), and Waist Hip Ratio (W/H ratio) showed a significant reduction in both groups. However, the study group had a larger mean difference than the control group. Conclusion: A combination of INY treatment protocol and CHB improves the glycaemic status and body composition parameters by enhancing the glucose utilization through cold-induced thermogenesis compared to that of INY treatment protocol alone.